Highly efficient S2−-adsorbed MoSx-modified TiO2 photocatalysts: A general grafting strategy and boosted interfacial charge transfer. (1st November 2020) - Gao, Duoduo; Yuan, Ranran; Fan, Jiajie; Hong, Xuekun; Yu, Huogen
Abstract: Exploiting efficient and low-cost cocatalyst with a facile grafting strategy is of critical importance for significantly boosting the photocatalytic H2 -evolution activity. In this study, S 2− -adsorbed MoS x nanoparticle as a superior H2 -evolutoin cocatalyst was successfully grafted on the TiO2 surface to greatly boost its photocatalytic activity via one-step lactic acid-induced synthesis strategy. Herein, the lactic acid can induce the homogeneous production of amorphous MoS x (a-MoS x ) nanoparticles from MoS4 2− precursor, while the symbiotic S 2- ions can be easily and availably self-adsorbed on the a-MoS x surface, resulting in the formation of S 2- -adsorbed a-MoS x nanoparticles with a small size of 0.5−3 nm. Photocatalytic results manifested that the S 2− -adsorbed MoS x nanoparticles could dramatically facilitate the H2 -generation rate of TiO2 photocatalysts (3452 μmol h -1  g -1, AQE = 16.5 %). In situ irradiated XPS in conjunction with transient-state PL and photoelectrochemical tests reveal that the improved H2 -generation activity can be ascribed to the synergistic effect of boosted interfacial charge transfer from TiO2 to S 2− -adsorbed MoS x and the superior H2 -evolution reaction on self-adsorbed S 2− ions. In addition, the S 2− -adsorbed MoS x nanoparticles can also act as the general H2 -generation cocatalyst to obviously promote the activity of other typical host photocatalysts such as g-C3 N4 and CdS. This work provides an innovative approach to develop high-efficiency MoS x -based cocatalyst with boosted interfacial charge transfer toward highly efficient photocatalytic materials.